2022
DOI: 10.3389/fragi.2022.897741
|View full text |Cite
|
Sign up to set email alerts
|

The Intestine as a Lifespan- and Proteostasis-Promoting Signaling Tissue

Abstract: In multicellular organisms such as Caenorhabditis elegans, cellular stress stimuli and responses are communicated between tissues to promote organismal health- and lifespan. The nervous system is the predominant regulator of cell nonautonomous proteostasis that orchestrates systemic stress responses to integrate both internal and external stimuli. This review highlights the role of the intestine in mediating cell nonautonomous stress responses and explores recent findings that suggest a central role for the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 98 publications
2
17
0
Order By: Relevance
“…Studies of systemic signaling in stress responses have shown that RNAi knock-down of hsp-90 mRNA in either the intestine or in neurons triggers upregulation of hsp-70 mRNA expression in muscle cells to promote thermotolerance, a phenomenon named ‘transcellular chaperone signaling’. 20,42,43 These effects were recently found to be HSF-1-independent, as are the effects we see here with CUL-6. Therefore, some of the thermotolerance benefits from CUL-6-mediated loss of HSP-90 protein may be due to cell non-autonomous signaling to muscle.…”
Section: Discussionsupporting
confidence: 88%
“…Studies of systemic signaling in stress responses have shown that RNAi knock-down of hsp-90 mRNA in either the intestine or in neurons triggers upregulation of hsp-70 mRNA expression in muscle cells to promote thermotolerance, a phenomenon named ‘transcellular chaperone signaling’. 20,42,43 These effects were recently found to be HSF-1-independent, as are the effects we see here with CUL-6. Therefore, some of the thermotolerance benefits from CUL-6-mediated loss of HSP-90 protein may be due to cell non-autonomous signaling to muscle.…”
Section: Discussionsupporting
confidence: 88%
“…HSPs are associated with protein misfolding and molecular chaperones involved in the stress response, specifically heat stress, hypoxia, and oxidative stress (Kyriakou et al, 2022, Murshid et al, 2013). During stress, HSPs are typically upregulated in the neurons and intestine as a part of the stress response (Hodge et al, 2022). Aβ+ worms exhibited elevated levels of four HSPs under all conditions: hsp-16 .…”
Section: Resultsmentioning
confidence: 99%
“…Stress resistance in C. elegans is a cell nonautonomous response mediated by communication between several tissues, most commonly the intestine and neurons (Hodge et al, 2022, Miller et al 2020, Chen et al 2024, Dutta et al, 2022). Stress leads to upregulation of transcription factors like hif-1 in neurons, which can activate serotonin signaling and other pathways in a cell nonautonomous manner (Hodge et al, 2022, Kyriakou et al, 2022, Miller et al 2020, Chen et al 2024, Dutta et al, 2022).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, DAF-16 activity in the gut partially restores daf-2 mutant longevity in daf-16; daf-2 mutants. There is evidence that this involves paracrine action via both DAF-16-dependent and -independent responses, involving alteration of gene expression 40, 41, 42 and of various processes in other tissues 43, 44, 45 , reviewed by 46 . Thus, the intestine may regulate aging in the whole organism via paracrine (and also autocrine) signaling.…”
Section: Discussionmentioning
confidence: 99%